Barriers to Efficient Foliar Uptake of dsRNA and Molecular Barriers to dsRNA Activity in Plant Cells - Bennett, Michael; Deikman, Jill; Hendrix, Bill; Iandolino, Alberto (Frontiers in Plant Science, 2020)
Foliar application of dsRNA to elicit an RNA interference (RNAi) response is currently under consideration as a crop protection strategy. To access the RNAi machinery of a plant, foliarly-applied dsRNAs must traverse the plant cuticle, avoid nuclease degradation, and penetrate the cell wall and plasma membrane. Application methods and co-formulants have been identified by Bayer Crop Science researchers and others that can help bypass barriers to dsRNA uptake in plants leading to an RNAi response in greenhouse grown, young plants and cell cultures. However, these advances in dsRNA delivery have yet to yield systemic RNAi silencing of an endogenous gene target required for product concepts such as weed control. Systemic RNAi silencing in plants has only been observed with the GFP transgene in N. benthamiana. Because biologically meaningful whole plant RNAi has not been observed for endogenous gene products in N. benthamiana or in other plant species tested, under growing conditions including field production, the regulatory risk assessment of foliarly-applied dsRNA-based products should not consider exposure scenarios that include systemic response to small RNAs in treated plants.